Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 3 - Section 3.11 - Hyperbolic Functions - 3.11 Exercises: 9

Answer

cosh(x) + sinh(x) = $e^{x}$

Work Step by Step

Use the definition of the hyperbolical cosine and sin; the divisor is the same, so it becomes a fraction sum. $$sinh(x) = \frac{e^{x} - e^{-x}}{2}$$ $$cosh(x) = \frac{e^{x} + e^{-x}}{2}$$ $ cosh(x) + sinh(x) = \frac{e^{x} - e^{-x}}{2} + \frac{e^{x} + e^{-x}}{2}$ = $\frac{2e^{x}}{2}$ = $e^{x}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.